Pre‐mRNA splicing repression triggers abiotic stress signaling in plants. (17th January 2017) - Ling, Yu; Alshareef, Sahar; Butt, Haroon; Lozano‐Juste, Jorge; Li, Lixin; Galal, Aya A.; Moustafa, Ahmed; Momin, Afaque A.; Tashkandi, Manal; Richardson, Dale N.; Fujii, Hiroaki; Arold, Stefan; et al.
Summary: Alternative splicing (AS) of precursor RNAs enhances transcriptome plasticity and proteome diversity in response to diverse growth and stress cues. Recent work has shown that AS is pervasive across plant species, with more than 60% of intron‐containing genes producing different isoforms. Mammalian cell‐based assays have discovered various inhibitors of AS. Here, we show that the macrolide pladienolide B (PB) inhibits constitutive splicing and AS in plants. Also, our RNA sequencing (RNA‐seq) data revealed that PB mimics abiotic stress signals including salt, drought and abscisic acid (ABA). PB activates the abiotic stress‐ and ABA‐responsive reporters RD29A::LUC and MAPKKK18::uidA in Arabidopsis thaliana and mimics the effects of ABA on stomatal aperture. Genome‐wide analysis of AS by RNA‐seq revealed that PB perturbs the splicing machinery and leads to a striking increase in intron retention and a reduction in other forms of AS. Interestingly, PB treatment activates the ABA signaling pathway by inhibiting the splicing of clade A PP2C phosphatases while still maintaining to some extent the splicing of ABA‐activated SnRK2 kinases. Taken together, our data establish PB as an inhibitor and modulator of splicing and a mimic of abiotic stress signals in plants. Thus, PB reveals the molecular underpinnings of the interplay between stress responses, ABA signaling and post‐transcriptional regulation in plants. Significance Statement: Alternative splicing (AS) of precursor RNAs can enhance transcriptome plasticity and proteome diversity in response to diverse growth and stress cues. Here we used an AS‐inhibiting drug (pladienolide B), previously used in mammalian cell culture, to uncover the interplay between stress responses, ABA signaling, and post‐transcriptional regulation in plants.